2015
DOI: 10.4103/1008-682x.148072
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of spermatogonial stem cells

Abstract: There have been significant breakthroughs over the past decade in the development and use of pluripotent stem cells as a potential source of cells for applications in regenerative medicine. It is likely that this methodology will begin to play an important role in human clinical medicine in the years to come. This review describes the plasticity of one type of pluripotent cell, spermatogonial stem cells (SSCs), and their potential therapeutic applications in regenerative medicine and male infertility. Normally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Thus, adult rSLCs form functional prostatic epithelium expressing normal histological and molecular characteristics when combined with fetal mouse UGM. These findings are similar to previous results showing that UGM recombined in heterotypic tissue recombinations with urinary bladder or vaginal epithelium (Cunha, 1975; Cunha et al , 1980; Cunha et al , 1983a) or spermatogonial stem cells (Simon et al , 2009; Cooke et al , 2015) could induce prostatic epithelial differentiation in these cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, adult rSLCs form functional prostatic epithelium expressing normal histological and molecular characteristics when combined with fetal mouse UGM. These findings are similar to previous results showing that UGM recombined in heterotypic tissue recombinations with urinary bladder or vaginal epithelium (Cunha, 1975; Cunha et al , 1980; Cunha et al , 1983a) or spermatogonial stem cells (Simon et al , 2009; Cooke et al , 2015) could induce prostatic epithelial differentiation in these cells.…”
Section: Discussionsupporting
confidence: 92%
“…The ability of rSLCs to differentiate into UtE under the inductive influence of neonatal UtM is similar to heterotypic tissue recombinations that have been reported previously for neonatal UtM recombined with neonatal vaginal epithelium (Cunha, 1976; Kurita et al , 2001), spermatogonial stem cells (Simon et al , 2009; Cooke et al , 2015) or aorta-derived mesangioblasts (Simon et al , 2013), all of which form morphologically and functionally normal uterine epithelium. Thus, various differentiated cell types can transdifferentiate into UtE expressing key markers for this tissue under the inductive influence of neonatal UtM.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…GC-1spg cells, a mouse spermatogonia-derived cell line, represent the differentiation state of type B spermatogonia or preleptotene spermatocytes [1,37]. Several studies have demonstrated GC-1spg cell plasticity [1,4,78,79]. In our study, we drove BMP9 expression using a recombinant adenovirus.…”
Section: Discussionmentioning
confidence: 99%